An Analysis of Students' Listening Anxiety in English as EFL Learners (A Case Study at the 2nd Semester of English Education Department in the State Islamic University Sultan Maulana Hasanuddin Banten - Nurhalisa, Siti Khodijah; Heryatun, Yayu; Sa'diah, Siti (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2023)
Listening is a complex processing in which the listeners take the incoming data, an acoustic signal, and interprets it based on a wide variety of linguistic and non-linguistic knowledge. The objective of this research is to find out the factors causes students’ listening anxiety in English as EFL learners at the 2nd Semester of English Education Department in the State Islamic University Sultan Maulana Hasanuddin Banten. This research used a descriptive qualitative method. The participants of this research were 28 students in class 2A. The instrument which is used in this research were observation, questionnaire and interview. The result of this research show that in the listening material factors, the students’ listening anxiety was caused by the speed rate, it is showed from 28 students there are 89,3% chose strongly agree with the statement. In lectures’ factors, the students’ listening anxiety caused by the lecturer show their frustration if the students do not know the answer, it is showed from 28 students there are 32,1% chose strongly agree with the statement. The last, in the students’ factors, the students listening anxiety caused by the environment around the student, if the environment around them is noisy they would distract and will missed the important point, it is showed from 28 students there are 50% students chose strongly agree with the statement. It can be concluded that the listening material factors are the most influential factors causing students' listening anxiety. The next influential factors are student factors, followed by lecturer factors.